Optimal groundwater management under climate change and technical progress - Quintana Ashwell, Nicolas E.; Peterson, Jeffrey M.; Hendricks, Nathan P. (My University, 2018)
We develop a dynamic model of groundwater extraction for irrigation where climate change and technical change are included as exogenous state variables in addition to the usual state variable of the stock of groundwater. Our key contributions are (i) an intuitive description of the conditions under which groundwater extraction can be non-monotonic, (ii) a numerical demonstration that extraction is non-monotonic in an important region overlying the Ogallala Aquifer, and (iii) the predicted gains from management are substantially larger after accounting for climate and technical change. Intuitively, optimal extraction is increasing in early periods when the marginal benefits of extraction are increasing sufficiently fast due to climate and technical change compared to the increase in the marginal cost of extraction. In contrast, most previous studies include the stock of groundwater as the only state variable and recommend a monotonically decreasing extraction path. We conduct numerical simulations for a region in Kansas overlying the Ogallala Aquifer and find that optimal groundwater extraction peaks 23 years in the future and the gains from management are large (29.5%). Consistent with previous literature, the predicted gains from management are relatively small (6.1%) when ignoring climate and technical change. The realized gains from management are not substantially impacted by incorrect assumptions of climate and technical change when formulating the optimal plan.
Citation: Quintana Ashwell, N. E., Peterson, J. M., & Hendricks, N. P. (2018). Optimal groundwater management under climate change and technical progress. Resource and Energy Economics, 51, 67–83. https://doi.org/10.1016/j.reseneeco.2017.10.005
Keywords: Climate change; Technical progress; Groundwater management; Optimal control